Modelling and control of heterogeneous photocatalytic reactors for VOC elimination - Chong, Siew Hui (Curtin University, 2009)
An increasing concern over the health issues arising from the accumulationof volatile organic compounds (VOCs) in an indoor environment hasmotivated substantial research efforts in the development of an abatementtechnology. The current research work is focused on the development ofvisible-light activated photo-reactors to eliminate or degrade the concernedair pollutants in an environmental-friendly and sustainable manner.The studies have been initiated by investigating the visible light driven photodegradationof acetone using several different photocatalysts—five in-housephotocatalysts and two commercial photocatalysts (e.g. Aeroxide P25). Lighttransmission plays a critical role in determining the efficiency ofphotocatalysts. Two types of batch reactors having different modes of lighttransmission have been investigated, namely the plastic optical-fibre reactor(OFR) and the fixed-bed reactor (FBR). In the latter, different catalyst-carrierswere compared (metal mesh, watch glass and Petri dish). The operation ofOFR was analysed in two modes by having the light rays parallel orperpendicular to the axis of the optical fibres. In the former, negligiblereaction was observed due to poor light transmission along the fibre length ormass transfer limitations due to thick coatings. However an appreciablereaction was noticed when the light rays were perpendicular to the axis, thusdirectly exposing the coated photocatalyst to the light. Regardless of theoperation mode, FBR fitted with Petri dish showed superiority (in terms ofease of handling and acetone conversion) over OFR and thus was utilised foranalysing the effectiveness of in-house photocatalysts.In the experiments carried out using FBR with Petri dish under visible-lightirradiation (with negligible UV), all studied photocatalysts including thecommercial ones demonstrated negligible acetone conversion. The exceptionwas the N,Pt-TiO2 (nitrogen and platinum-codoped TiO2) which achievedabout 40% acetone conversion within 40-minute irradiation period. Therefore,N,Pt-TiO2 was chosen and employed in the continuous-flow reactor. The novel continuous-flow reactor offered high surface area available for catalystcoating, multiple channels to provide ample contact time, and flexibility tochange the catalyst and catalyst carrier. Two experimental methods werecarried out to investigate the degradation of toluene (100 ppmv in air) usingsix 10-W fluorescent tubelamps. The novel method was shown to beadvantageous over the conventional method due to the reduced amount oftoluene loaded on catalyst. The major challenge has been the catalyst decayproblem. Using a contact time of 12 minutes, in the first 3.5 hours, the reactorestablished 49% of conversion, which then decreased to 38% in the next 4hours and finally no conversion was observed in 120 hours.Due to scarce information on the coupling of radiation and reaction modelswith the porous media formulations in FLUENT, a novel approach formodelling the local radiation intensity across a porous medium has beenproposed. To validate this approach, the published experimental work on amonolith photoreactor carried out by Hossain et al. (1999) was used. Thissemi-empirical simulation approach showed a good fit to the experimentaldata. In addition to FLUENT simulation, a phenomenological model involvingthe LH kinetics, plug-flow reactor (PFR) model and a modified linear-sourcesphericalemission (LSSE) model was developed. The key feature of thismodel is that despite its simplicity, the LSSE model was modified to includethe effect of reactor wall reflectivity. The model results were in a reasonableagreement with the experimental data (14% over-prediction and slightscattering of data points).